DISCOURSE ON ZAKAT REGULATION IN THE MANAGEMENT OF ZAKAT IN INDONESIA - Rahman, Holilur; Busro, Busro (Universitas Al-Amien Prenduan, 2020)
This paper argues that the Indonesian government (President, Peoplesâ€™ Representative Council/DPR, Ministry of Religious Affairs (MORA), and localÂ Â government) has an important role in distributing social welfare to Muslim public (Muslim society) by stipulating official regulations, which authoritize the National Board of Zakat Managers (Badan Amil Zakat Nasional) to manage zakat in Indonesia. We call these regulations â€œqadaâ€™iâ€ (ketetapan negara), while we dub the normative set of laws from the Qurâ€™an and Hadith (utterances ascribed to the Prophet Muhammad) â€œdiyani/obedience).